Design of Comfortable Structure of Junior High School Building By Using ETABS Software - Malfazan Abda'u malfazan; Muhammad Azrial Akbar; Sudarno Sudarno; Arief Firmanto (CV. Syntax Corporation Indonesia, 2024)
Ibnu Abbas Foundation intends to build a four-story school building for junior high school in Talun District, Cirebon Regency. This study aims to design a school building structure that is comfortable, safe, and meets earthquake-resistant standards using ETABS software. The design process includes structural planning, analysis of building response to static and dynamic loads such as dead load, live load, wind load, and earthquake load, as well as detailed design of structural elements such as floors, columns, beams, and foundations. This research method uses a calculation approach that refers to the applicable Indonesian National Standards (SNI), namely SNI 2847: 2019 for structural planning, SNI 1727: 2020 for load planning, and SNI 1726: 2019 for earthquake resistant planning. The planning process uses the Response Spectrum SRPMK method and is assisted by ETABS software for structural analysis and design. The planning results show that the four-story school building structure can be built safely using a pile foundation with a depth of 4.4 meters and diameters of 50 and 60 cm. The foundation is able to withstand the load of the planned structure. The structural elements of the school building are planned using reinforced concrete with a material quality of K-300 for the frame and K-350 for the columns. The main reinforcement used is BJTS 420A, and the transverse reinforcement is BJTP 280.